Current antimicrobial susceptibility pattern among blood culture isolates of Salmonella enterica serovar Typhi in Muzaffarabad, Pakistan - Khan, Mumtaz Ahmad; Farid, Jamila; Idris, Muhammad; Khan, Muhammad Ijaz; Mumtaz, Sehrish; Sadiq, Muhammad Shakil (Pakistan Journal of Physiology, 2020)
Background: Antibiotic resistance is a major problem in Salmonella enterica serovar Typhi (S Typhi). The resistance has developed to three first line drugs (ampicillin, chloramphenicol, and trimethoprim-sulfamethoxazole) in early 1980s, and labelled as multidrug resistant (MDR). The aim of this study was to determine the current susceptibility pattern of S Typhi in our setup. Method: This prospective study was carried out in Department of Microbiology, Abbas Institute of Medical Sciences, Muzaffarabad from January 2018 to December 2019. All blood culture samples from febrile patients were inoculated in Oxoid Signal blood culture system (Remel, Lenexa KS) and incubated at 37 °C. Positive culture bottles were sub cultured on blood agar and MacConkey agar, and incubated for overnight at 37 °C. The isolates were identified as S Typhi by colony morphology, serotyping, and biochemical tests using API 20E. Susceptibility testing was performed using the Modified Kirby Bauer disk diffusion method. All XDR isolates were confirmed by determining MICs of ciprofloxacin and ceftriaxone by using the E-test strips. Results: A total of 360 blood culture specimens were submitted, 146 (40.5%) specimens yielded growth of S Typhi. The resistance rates of S Typhi for ampicillin, chloramphenicol and trimethoprim-sulfamethoxazole were 82%, 88% and 89% respectively. Percentage of MDR isolates in S Typhi was found very high (108, 74% isolates). High rate of resistance (78, 53% isolates) was found to ciprofloxacin. Frequency of XDR isolates in S Typhi was high (40, 27% isolates). All isolates were found sensitive to azithromycin and meropenem. Pak J Physiol 2020;16(3):14–7